Layer by Layer Composite Membranes of Alginate-Chitosan Crosslinked by Glutaraldehyde in Pervaporation Dehydration of Ethanol - Nur Rokhati; Titik Istirokhatun; Asep Muhamad Samsudin (International Journal of Renewable Energy Development, 2016)
Hydrophilicity of membrane causing only water can pass through membrane. Pervaporation process using organophilic membrane has been offered as alternative for ethanol dehydration. This paper investigate pervaporation based biopolymer composite membrane from alginate-chitosan using layer by layer method prepared by glutaraldehyde as crosslinking agent and polyethersulfone (PES) as supported membrane. Characterization of crosslinked of composite membrane by FTIR helped in identification of sites for interaction between layers of membrane and support layer (PES). The SEM showed a multilayer structure and a distinct interface between the chitosan layer, the sodium alginate layer and the support layer. The coating sequence of membranes had an obvious influence on the pervaporation dehydration performance of membranes. For the dehydration of 95 wt% ethanol-water mixtures, a good performance of PES-chitosan-alginate-chitosan (PES/Chi/Alg/Chi) composite membrane was found in the pervaporation dehydration of ethanol. Article History: Received April 12nd , 2016; Received in revised form June 25th , 2016; Accepted July 1st , 2016; Available onlineHow to Cite This Article: Rokhati, N., Istirokhatun, T. and Samsudin, A.M. (2016) Layer by Layer Composite Membranes of Alginate-Chitosan Crosslinked by Glutaraldehyde in Pervaporation Dehydration of Ethanol. Int. Journal of Renewable Energy Development, 5(2), 101-106.http://dx.doi.org/10.14710/ijred.5.2.101-106